Baby-sitters little sister. Volume 5 : Karen's school picture : a graphic novel - Martin, Ann M., 1955-; Farina, Katy (Baby-sitters little sister (Graphix (Firm)), 2022)
Karen has to get glasses! She doesn't want them, especially because school pictures are going to be taken soon. But she picks out some pretty pink ones and thinks she looks very grown-up. Then Yicky Ricky at school starts calling her names, like Owl Girl and Googly Eyes. If Karen wears her glasses for the school picture, Ricky will make fun of her.